2000
DOI: 10.5488/cmp.3.4.749
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURE SIMILARITY AND LATTICE DYNAMICS OF InSe AND In_4Se_3 CRYSTALS

Abstract: In the work it was shown that the In 4 Se 3 crystal is similar by its dynamical properties to the InSe modulated crystal. The transformation of the D group of In 4 Se 3 structure has been investigated. In spite of structure corrugation of In 4 Se 3 layer, it is shown that the region of the weak bond in this crystal by the dynamical characteristics is similar to the weak bond region in InSe crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The similar values were calculated from LEED experimental data shown on Fig. 1 e, f. Such derived values correlates well with the same for the bulk InSe [14].…”
Section: Resultssupporting
confidence: 88%
“…The similar values were calculated from LEED experimental data shown on Fig. 1 e, f. Such derived values correlates well with the same for the bulk InSe [14].…”
Section: Resultssupporting
confidence: 88%
“…Lin et al noticed that the Pb and Sn substitute at different In-sites (In4 and In2 sites respectively) when they re-examine the formation energy calculation of In 4 Se 3 [27]. The crystal structure of In 4 Se 3 consists of In 1+ cations and [(In 3 ) 5+ (Se 3 ) 6− ] 1− anionic staking layers along the a -axis [35,38,39]. …”
Section: Resultsmentioning
confidence: 99%
“…Compared to the atomic radius of selenium, the slightly smaller chlorine atom may be more easily occupied at the Se site in the lattice of the 4:3 indium selenide than the much smaller fluorine, the same size bromine, and the larger iodine atom. It has been reported that the crystal structure of In 4 Se 3 consists of [(In 3 ) 5+ (Se 3 ) 6− ] 1− anionic layers (Se1, Se2, Se3 sites) and In 1+ cations with a weak van der Waals interaction along the a -axis between the layers and strong covalent-ionic interaction in the bc -planes within the layer [ 17 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent theoretical calculations by Bercha et al concentrated on the peculiarities of the band structure, phonon spectrum, and lattice dynamics of crystalline In 4 Se 3 . [22][23][24] …”
Section: Crystalline In X Se Y Structuresmentioning
confidence: 99%